2014
DOI: 10.1073/pnas.1403466111
|View full text |Cite
|
Sign up to set email alerts
|

Climate change underlies global demographic, genetic, and cultural transitions in pre-Columbian southern Peru

Abstract: Several archaeological studies in the Central Andes have pointed at the temporal coincidence of climatic fluctuations (both longand short-term) and episodes of cultural transition and changes of socioeconomic structures throughout the pre-Columbian period. Although most scholars explain the connection between environmental and cultural changes by the impact of climatic alterations on the capacities of the ecosystems inhabited by pre-Columbian cultures, direct evidence for assumed demographic consequences is mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 51 publications
2
62
0
3
Order By: Relevance
“…Previous ancient DNA studies, including the samples analyzed, found clear evidence of population continuity in western South America, or the Central Andes, in the monitored time frame based on mitochondrial, autosomal, y-chromosomal markers (Kemp et al 2009;Carnese et al 2010;Fehren-Schmitz et al 2010;Fehren-Schmitz et al 2011;Fehren-Schmitz et al 2014;Fehren-Schmitz et al 2015). Studies of uniparental inherited and genome-wide genetic markers link these ancient populations to the modern population of the Central Andes (Bisso-Machado et al 2012; Lewis et al 2007;Reich et al 2012;Wang et al 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous ancient DNA studies, including the samples analyzed, found clear evidence of population continuity in western South America, or the Central Andes, in the monitored time frame based on mitochondrial, autosomal, y-chromosomal markers (Kemp et al 2009;Carnese et al 2010;Fehren-Schmitz et al 2010;Fehren-Schmitz et al 2011;Fehren-Schmitz et al 2014;Fehren-Schmitz et al 2015). Studies of uniparental inherited and genome-wide genetic markers link these ancient populations to the modern population of the Central Andes (Bisso-Machado et al 2012; Lewis et al 2007;Reich et al 2012;Wang et al 2007).…”
Section: Discussionmentioning
confidence: 95%
“…DNA was extracted from the teeth samples employing the protocol described in Fehren-Schmitz et al (2014. At least two independent extracts were made for each sample to allow an authentication of analysis results by comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Shimada et al 1991, Schimmelman et al 2003Marchant et al 2004;Sandweiss et al 2007;Sandweiss, Richardson III 2008;Reindel, Wagner 2009;Reindel 2009) and that the effect of large-scale environmental processes on human societies was not uniform (Mächtle, Eitel 2013). Particularly intriguing is the almost simultaneous abandonment of permanent settlements in Lomas de Lachay at the end of the Early Intermediate Period and fall of the Nazca culture on the South Coast of Peru due to an increased variability of precipitation (Fehren-Schmitz et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Peruvian civilizations migrated between coastal valleys and the Andean highlands between ad 640 and 1200. Historical climate records and mitochondrial DNA sequences extracted from the bones of people who lived there showed that coastal droughts and flash floods pushed the populations to move to the mountains, from where they returned when droughts afflicted those lands 5 . Other studies have reported a higher incidence of conflict since 1950 among communities experiencing changes in climate -cases rose by a few per cent for each standard-deviation increase in temperature or rainfall 3 .…”
Section: Assessing Influencementioning
confidence: 99%